Empirical Study on OEE Optimization in a Peruvian Flexographic Printing SME: A Lean-TPM Model Integrating 5S and SMED - Quiroz-Flores, Juan Carlos; Reynaga-Vásquez, Bryan; Chávez-Revoredo, Enrique (LACCEI, 2025)
The flexographic printing industry plays a crucial role in packaging, yet many companies in emerging markets struggle with low Overall Equipment Effectiveness (OEE), primarily due to long setup times, unplanned downtimes, and process inconsistencies. Previous studies have addressed these issues through isolated applications of Total Productive Maintenance (TPM), Single-Minute Exchange of Dies (SMED), and 5S. However, limited research has integrated these tools into a unified model tailored to the sector’s challenges. This study developed a structured Lean-TPM model combining 5S, SMED, and TPM to enhance OEE in a Peruvian flexographic printing SME. The model was validated through pilot implementations and simulation using Arena software. Results showed an OEE increase from 59.91% to 70.84%, setup time reduction by 29.05%, and defect rate decrease by 28.26%. These improvements demonstrate the model’s effectiveness in optimizing performance while ensuring financial sustainability. This research provides a replicable framework for similar industries. Future studies should explore artificial intelligence applications to further enhance predictive maintenance and operational efficiency in dynamic manufacturing environments.